The effect of nutrition education on weight gain in pregnant women with chronic energy deficiency (CED) - Yeni Friska Sinulingga; Evlindari Sentani Daulay; Endang Sihaloho; Hudeni Rizki; Ristiani Ristiani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Chronic Energy Deficiency (CED) in pregnant women remains a public health problem in Indonesia and contributes to an increased risk of pregnancy complications, low birth weight, stunting, and maternal and perinatal mortality. One effort to improve the nutritional status of pregnant women with CED is through structured and ongoing nutrition education. Purpose: This study aims to determine the effect of nutritional education on weight gain in pregnant women with Chronic Energy Deficiency (CED). Method: This study used a pre-experimental design with a one-group pretest–posttest approach. The study was conducted at the Helen Tarigan Clinic from March to May 2025. A sample of 25 pregnant women with special needs was selected using a total sampling technique. The intervention, in the form of nutritional education, was provided in a structured manner through counseling and educational media. Weight data were measured before and after education, then analyzed using a paired t-test with a significance level of p < 0.05. Results: The average weight of pregnant women before nutrition education was 45.2 ± 2.8 kg and increased to 47.1 ± 2.7 kg after education. There was a difference in weight gain of 1.9 kg. The statistical test results showed a p-value of 0.001, indicating a significant effect of nutrition education on weight gain in pregnant women with CED. Conclusion: Nutrition education has a significant impact on weight gain in pregnant women with Chronic Energy Deficiency, so it is important to implement it as part of antenatal care.